Implementation of Protection for Non-Organised Orphans by The Mosque Prosperity Agency (Study on BKM Nurul Hidayah and BKM Silaturrahim) - Purba, Nelvitia; Annisa, Isdy (Universitas Medan Area, 2025)
This article aims to determine the implementation of child protection laws in protecting non-orphanage orphans based on Law No. 35 of 2014. The problem focuses on the implementation by the Nurul Hidayah Mosque welfare agency and BKM Silaturrahim, obstacles and efforts to overcome obstacles in providing protection for orphans. To approach the problem, the theory of legal protection is used. Secondary data is obtained from secondary legal materials in the form of books, laws and regulations and primary data obtained directly from the field through interviews and analyzed qualitatively. This study concludes that the implementation of protection for non-orphanage orphans by BKM in practice is community-oriented. Considering that non-orphanage orphans live in the community (not in official orphanage institutions), the strategy taken is more focused on social support, economic assistance, and protection initiated by the local community. BKM Silaturrahim in practice have implemented basic child care in the form of cash and school supplies. Meanwhile, for Social and Psychological Protection in BKM Silaturrahum, it is already visible with the existence of a Madrasah for these children.